1993
DOI: 10.1073/pnas.90.5.1814
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transforming growth factor beta is elevated in human and experimental diabetic nephropathy.

Abstract: Diabetes is now the most common cause of progressive kidney failure leading to dialysis or transplantation. The central pathological feature of diabetic nephropathy is accumulation of extracellular matrix within the glomeruli. The factors in the diabetic milieu responsible for extracellular matrix accumulation are not understood. Here we report that in glomeruli of rats made diabetic there is a slow, progressive increase in the expression of transforming growth factor 1B (TGF-3) mRNA and TGF-,3 protein. A key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
465
2
6

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 782 publications
(493 citation statements)
references
References 48 publications
20
465
2
6
Order By: Relevance
“…Furthermore, in porcine and rat mesangial cells the addition of glucosamine [6,7], a precursor of the HBP, or over-expression of GFAT [8] increases TGFβ1 expression, a key factor in the pathogenesis of diabetic glomerulosclerosis [9,10,11,12,13]. However, there is currently no information on the role of the HBP in the induction of TGFβ1 expression in human renal cells or on the intracellular signalling pathways involved.…”
mentioning
confidence: 99%
“…Furthermore, in porcine and rat mesangial cells the addition of glucosamine [6,7], a precursor of the HBP, or over-expression of GFAT [8] increases TGFβ1 expression, a key factor in the pathogenesis of diabetic glomerulosclerosis [9,10,11,12,13]. However, there is currently no information on the role of the HBP in the induction of TGFβ1 expression in human renal cells or on the intracellular signalling pathways involved.…”
mentioning
confidence: 99%
“…The prosclerotic cytokine transforming growth factor beta (TGF-β1) has been implicated as an important downstream mediator in the progression of the renal pathological changes occurring in diabetic patients which lead to glomerular and tubular basement membrane thickening, mesangial matrix expansion, and glomerulosclerosis [13,15,15,16,17,18]. Numerous studies including data from our own laboratory indiStudies have provided evidence that angiotensin-converting enzyme inhibitors and angiotensin-receptor antagonists attenuate diabetic glomerulosclerosis and slow the progression of diabetic kidney disease [1, 2, cate that hyperglycemia induces an increase in TGF-β1 protein and mRNA expression in experimental and human diabetes [15,19,20,21] and in cultured mesangial cells [22,23,24].…”
mentioning
confidence: 99%
“…Numerous studies including data from our own laboratory indiStudies have provided evidence that angiotensin-converting enzyme inhibitors and angiotensin-receptor antagonists attenuate diabetic glomerulosclerosis and slow the progression of diabetic kidney disease [1, 2, cate that hyperglycemia induces an increase in TGF-β1 protein and mRNA expression in experimental and human diabetes [15,19,20,21] and in cultured mesangial cells [22,23,24]. Although previous investigations clearly demonstrated that ang II stimulates the synthesis of extracellular matrix proteins through an enhanced TGF-β1 expression in mesangial cells [25] the molecular mechanism of ang II-induced TGF-β1 gene activation, particularly the detailed localization of the ang II responsive elements on the TGF-β1 promoter, have not been studied yet.…”
mentioning
confidence: 99%
“…In addition to this study, a lot of basic research has discovered the mechanisms between dyslipidemia and diabetic nephropathy [14]. Studies revealed that transforming growth factor-b signaling [15], renin-angiotensin system [16], S100A8/TLR4 signaling [17], and oxidative stress [18] may play an important role in the progression of diabetic nephropathies. Concerning the development of albuminuria, the importance of the deterioration of glycocalyx, which is on the surface of endothelium, was highlighted [19].…”
Section: Dyslipidemia and Loss Of Renal Functionmentioning
confidence: 89%